2014
DOI: 10.1186/1479-5876-12-200
|View full text |Cite
|
Sign up to set email alerts
|

Aurora-A contributes to cisplatin resistance and lymphatic metastasis in non-small cell lung cancer and predicts poor prognosis

Abstract: BackgroundPlatinum-based chemotherapy improves survival among patients with non-small cell lung cancer (NSCLC), but the efficiency is limited due to resistance. In this study, we aimed to identify the expression of Aurora-A and its correlation with cisplatin resistance and prognosis in NSCLC.MethodsWe used immunohistochemical analysis to determine the expression of Aurora-A protein in 102 NSCLC patients treated by surgery and adjuvant cisplatin-based chemotherapy. The prognostic significances were assessed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 45 publications
2
50
0
Order By: Relevance
“…All eligible studies were published between 2005 and 2014. All TNM Stages (I-IV) were considered in 18 studies (46.2%) (9,18,20,27,28,30,(34)(35)(36)(37)(38)40,43,44,50,55,56,58), non-metastatic solid tumors (including Stage I-III or localized disease, based solely on singlestage disease or mixture of tumor stages) were considered in 12 (30.8%) studies (22,29,31,33,39,41,42,46,48,51,53,54); metastatic solid tumors (Stage IV) patients were considered in four studies (10.2%) (23,45,49,57); disease stage was not available were considered in five studies (12.8%). Four studies analyzing AURKA mRNA expression used real-time reverse transcription PCR (RT-PCR) (20,34,35,45); one study analyzing AURKA gene amplification by fluorescence in situ hybridization (FISH) (54); the other one used immunohistochemical (IHC) staining and RT-PCR (47); and the remaining 33 studies applied a immunohistochemistry detection method (9,18,19,21-23,27-33, 36-44,46,48-53,55-58).…”
Section: Characteristics Of Identified Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…All eligible studies were published between 2005 and 2014. All TNM Stages (I-IV) were considered in 18 studies (46.2%) (9,18,20,27,28,30,(34)(35)(36)(37)(38)40,43,44,50,55,56,58), non-metastatic solid tumors (including Stage I-III or localized disease, based solely on singlestage disease or mixture of tumor stages) were considered in 12 (30.8%) studies (22,29,31,33,39,41,42,46,48,51,53,54); metastatic solid tumors (Stage IV) patients were considered in four studies (10.2%) (23,45,49,57); disease stage was not available were considered in five studies (12.8%). Four studies analyzing AURKA mRNA expression used real-time reverse transcription PCR (RT-PCR) (20,34,35,45); one study analyzing AURKA gene amplification by fluorescence in situ hybridization (FISH) (54); the other one used immunohistochemical (IHC) staining and RT-PCR (47); and the remaining 33 studies applied a immunohistochemistry detection method (9,18,19,21-23,27-33, 36-44,46,48-53,55-58).…”
Section: Characteristics Of Identified Studiesmentioning
confidence: 99%
“…One or more oncologic outcome parameters were analyzed on multivariate analysis in 33 studies (9,(18)(19)(20)(21)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)58). A significant association between high AURKA expression and the poor prognosis of patients was reported in 71.4% of studies on OS (9,18,31,32,(34)(35)(36)(37)39,(42)(43)(44)(45)48,(50)(51)(52)(53)…”
Section: Characteristics Of Identified Studiesmentioning
confidence: 99%
“…12 The inhibition of Aurora A kinase causes DNA damage and renders cancer cells more sensitive to radiation. [13][14][15][16][17] Cancer cells responds to DNA damage by initiating the DNA-damage response, which induces cell cycle delay, more prolonged growth arrests and apoptosis of the lethally damaged cells. Gamma-H2AX is involved in recruitment of DNA damage repair factors to sites of double-strand breaks (DSB).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we found that Aurora kinase inhibitor ZM induced mitotic slippage and resistant polyploidy in acute myeloid leukemia cells [30]. We further found that pan-Aurora kinase (-A and -B) inhibitor ZM [31], but not Aurora A inhibitor MLN8237 [32, 33], induced polyploidy in breast cancer (for all online suppl. material, see www.karger.com/doi/10.1159/000480322, Fig.…”
Section: Resultsmentioning
confidence: 83%